AA. VV. - Cartha: On Relations in Architecture - LÓPEZ RIVERA, FRANCISCO JAVIER (ZARCH, 2017)
AA. VV.Cartha: On Relations in ArchitecturePark Books, Zúrich, 2016, 274 págs.Idioma: inglés. Tapa dura. Dimensiones: 19 x 2,5 x 24,1 cm. 22 €. ISBN: 978-3-03860-037-4